Cytoarchitectureal changes in hippocampal subregions of the NZB/W F1 mouse model of lupus - J.-M. Graïc; L. Finos; V. Vadori; B. Cozzi; R. Luisetto; T. Gerussi; Gatto M; A. Doria; E. Grisan; L. Corain; A. Peruffo (Brain, Behavior, & Immunity - Health, 2023)
Over 50% of clinical patients affected by the systemic lupus erythematosus disease display impaired neurological cognitive functions and psychiatric disorders, a form called neuropsychiatric systemic lupus erythematosus. Hippocampus is one of the brain structures most sensitive to the cognitive deficits and psychiatric disorders related to neuropsychiatric lupus. The purpose of this study was to compare, layer by layer, neuron morphology in lupus mice model NZB/W F1 versus Wild Type mice.By a morphometric of cells identified on Nissl-stained sections, we evaluated structural alterations between NZB/W F1 and Wild Type mice in seven hippocampal subregions: Molecular dentate gyrus, Granular dentate gyrus, Polymorph dentate gyrus, Oriens layer, Pyramidal layer, Radiatum layer and Lacunosum molecular layer. By principal component analysis we distinguished healthy Wild Type from NZB/W F1 mice. In NZB/W F1 mice hippocampal cytoarchitecture, the neuronal cells resulted larger in size and more regular than those of Wild Type. In NZB/W F1, neurons were usually denser than in WT. The Pyramidal layer neurons were much denser in Wild Type than in NZB/W F1. Application of principal component analysis, allowed to distinguish NZB/W F1 lupus mice from healthy, showing as NZBW subjects presented a scattered distribution and intrasubject variability.Our results show a hypertrophy of the NZB/W F1 hippocampal neurons associated with an increase in perikaryal size within the CA1, CA2, CA3 region and the DG. These results help advance our understanding on hippocampal organization and structure in the NZB/W F1 lupus model, suggesting the hypothesis that the different subregions could be differentially affected in neuropsychiatric systemic lupus erythematosus disease. Leveraging an in-depth analysis of the morphology of neural cells in the hippocampal subregions and applying dimensionality reduction using PCA, we propose an efficient methodology to distinguish pathological NZBW mice from WT mice.”